Treino de atividades de vida diária em crianças com autismo: um estudo sobre o efeito do treino convencional e da intervenção a partir de um software - SENA, José Lucas Oliveira de Sena (2023)
The ASD is a developmental disorder that, in the midst of a set of symptoms presented, from early childhood, limits or harms the development of daily tasks. In this setting, it is understood the relevance of the occupational therapist to glimpse actions in the daily life that generate possibilities and stimulate potentialities of the subject, in order to favor their engagement in occupations and their occupational performance. The objective of this study was to compare the effect of the combined use of conventional daily life activities (ADLs) and the software intervention with their use on the occupational performance of children with ASD in the activities of brushing, dressing and undressing. This is a qualitative study of a single subject experimental design, based on baseline and post-test analysis in a sample of four children diagnosed with ASD. It was used as research instruments: a) semi-structured interview, b) Childhood Autism Rating Scale (CARS) scale, c) self-care scale included in the Pediatric Evaluation of Disability Inventory Protocol (PEDI), and d) record sheets. This research presented favorable results regarding the gain of functional abilities from the training of the ADLs of dressing, undressing and brushing the teeth in four children with ASD. Although that the conventional training and the combined training were those that presented the best results through teaching, learning and generalization in the activities in question. It is estimated that this study contribute to the systematization of the training of ADLs in children with autism, instigating possibilities of interventions from the computerization added to the conventional intervention. In addition, to enable approximations of Occupational Therapy and analysis of behavior in the therapeutic process.